2017
DOI: 10.1016/j.urolonc.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Implication of VHL, ERK5, and HIF-1alpha in clear cell renal cell carcinoma: Molecular basis

Abstract: Objectives: To determine the expression status of several proteins related to VHL gene function and its relationship with common clinicopathological parameters.Material and methods: Observational, analytical, cross-sectional study with 50 patients diagnosed with clear cell renal cell carcinoma. The study analyzed VHL mutations and hypermethylation as well as protein expression of VHL, CA-IX, HIF-1alpha, VEGF, ERK1/2, and ERK5, relating them to clinical variables.A bivariate and multivariate descriptive logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Moreover, an association of high ERK5 expression with advanced tumor stage and the presence of lymph node metastases has been reported in a subset of patients, linking ERK5 to an invasive phenotype in this cancer [100]. Similarly, although a functional role of ERK5 has not been demonstrated, an observational study with 50 patients diagnosed with CCRC showed that ERK5 expression is increased in 58% of cases and is associated with the presence of metastasis and more advanced stages [101].…”
Section: Activating Invasion and Metastasismentioning
confidence: 99%
“…Moreover, an association of high ERK5 expression with advanced tumor stage and the presence of lymph node metastases has been reported in a subset of patients, linking ERK5 to an invasive phenotype in this cancer [100]. Similarly, although a functional role of ERK5 has not been demonstrated, an observational study with 50 patients diagnosed with CCRC showed that ERK5 expression is increased in 58% of cases and is associated with the presence of metastasis and more advanced stages [101].…”
Section: Activating Invasion and Metastasismentioning
confidence: 99%
“…ERK5 positively regulates cell proliferation via p21 inhibition and cell survival via BCL2 expression in endothelial cells [ 25 , 26 , 27 , 28 , 29 ]. Several reports showed that strong ERK5 expression indicates worse prognoses in breast, prostate cancer, and ccRCC [ 12 , 13 , 30 , 31 ]. In addition, recent studies demonstrated ERK5 as a potential therapeutic target in leukemia, multiple myeloma, breast, liver, prostate, and pancreatic cancer [ 25 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that ERK5 is degraded through the ubiquitin–proteasome system in a process mediated by a VHL protein (pVHL) [ 11 ] because harboring an inactivation of pVHL, ccRCC should store ERK5. In fact, a previous report demonstrated that 60% of ccRCC patients had overexpression of ERK5 in their surgical specimens [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arias et al confirmed that increased ERK5 levels foster proliferation, invasion, and metastasis in clear cell renal cell carcinoma, with a positive correlation between ERK5 expression and the disease's invasiveness and metastasis in fresh human samples [81]. Another study identified a connection between ERK5 and enhanced metastasis and advanced disease stages [130]. A clinical investigation underscored ERK5's prognostic significance in renal cell carcinoma, where patients with elevated ERK5 expression experienced poorer outcomes [131].…”
Section: Kidney and Livermentioning
confidence: 96%